A Uji Sensori Minuman Serbuk Berbasis Ekstrak Buah - Mardhyah Divani; Wiwik Indrayeni (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
The development of increasingly modern times and increasing social welfare have encouraged changes in human lifestyles. This change occurs in food and drink patterns. One alternative used in making practical drinks is to make it in powder form. The advantages of powdered drinks are their practical presentation, long shelf life due to the low water content. The aim of this research is to determine the process of making drinks in powder form using the crystallization method, to determine the product results in terms of color, aroma and taste, and to determine the acceptability of powdered beverage products. The research method involves carrying out experiments with 3 repetitions on 2 types of fruit, namely pineapple and beetroot, so as to obtain the desired results, including conducting sensory tests in terms of color, aroma, texture and taste. This research was conducted at the Culinary Workshop, Padang State University. The results of the organoleptic test of powdered drinks using pineapple and beetroot describe the color quality of powdered drinks made from white pineapple and the color of powdered drinks made from purple beetroot, the texture quality of powdered drinks made from pineapple and fine beetroot, the aroma quality of powdered drinks made from fruit fragrant pineapple and beetroot, quality taste of powdered drink from pineapple and sweet beetroot. Keywords: Powdered Drink, Beetroot, Pineapple, Quality